Glass Containers, Classification of Their Composition, Characteristics - Nadirova Dildorakhan Qudratkho'dja’s Qizi; Azizov Olimjon Tahirovich (Zien Journals, 2022)
In this article, the composition, classification, properties of glass containers were studied in depth and the results were highlighted.
Keywords: glass container; composition of glass; functionality